2019
DOI: 10.2471/blt.18.227876
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and vision screening for preschool children using mobile technology, South Africa

Abstract: ObjectiveTo implement and evaluate a community-based hearing and vision screening programme for preschool children in the Western Cape, South Africa, supported by mobile health technology (mHealth) and delivered by community health workers (CHWs).MethodsWe trained four CHWs to provide dual sensory screening in preschool centres of Khayelitsha and Mitchells Plain during September 2017–December 2018. CHWs screened children aged 4–7 years using mHealth software applications on smartphones. We used logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(114 citation statements)
references
References 30 publications
6
108
0
Order By: Relevance
“…A high follow-up attendance rate (89.4%) for hearing screening was also found in a recent South African community-based study when the rescreening was conducted at a communitylevel as opposed to a public healthcare institution. 29 Patients who needed referral to the tertiary hospital for specialised diagnostic assessment had an attendance rate of 73.3%, which is in line with a previous South African community-based hearing screening study that found an attendance rate for diagnostic assessments of 75.8%. 29 Patient travelling distance was significantly shorter to the district hospital as opposed to the tertiary hospital.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A high follow-up attendance rate (89.4%) for hearing screening was also found in a recent South African community-based study when the rescreening was conducted at a communitylevel as opposed to a public healthcare institution. 29 Patients who needed referral to the tertiary hospital for specialised diagnostic assessment had an attendance rate of 73.3%, which is in line with a previous South African community-based hearing screening study that found an attendance rate for diagnostic assessments of 75.8%. 29 Patient travelling distance was significantly shorter to the district hospital as opposed to the tertiary hospital.…”
Section: Discussionsupporting
confidence: 87%
“…29 Patients who needed referral to the tertiary hospital for specialised diagnostic assessment had an attendance rate of 73.3%, which is in line with a previous South African community-based hearing screening study that found an attendance rate for diagnostic assessments of 75.8%. 29 Patient travelling distance was significantly shorter to the district hospital as opposed to the tertiary hospital. Access to services is one of the leading barriers to hearing healthcare in underserved communities.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These studies described results of audiologists along with trained facilitators at remote sites that provided hearing screening services for infants and children. Eksteen et al (2019) reported that use of minimally trained community care workers (CCW) to screen for both hearing and vision was affordable (estimated cost $5.63 USD per child) and provided a scalable service delivery model. Monica et al (2017) assessed the feasibility of synchronous remote tele-hearing screening using audiometry and distortion product otoacoustic emissions (DPOAE) on a small group of school children (n ¼ 31) in India.…”
Section: Screening Studiesmentioning
confidence: 99%
“…13,14 This issue also suggests potential solutions that seek to integrate ear and hearing care within the overall spectrum of services provided through health systems, and focuses on building capacity of health-care providers in ear and hearing care. 10,11 Papers present technological solutions that can improve access to hearing care and facilitate its integration into health systems 15,16 and provide examples of innovative policies that could serve as models for improving access to services in underserved areas of the world. 6,12 The theme issue sets the stage for the First Membership Assembly of the World Hearing Forum, which will take place this December at WHO headquarters in Geneva, Switzerland.…”
mentioning
confidence: 99%